Technical means for objectification of medical treatments in the area of the deep stabilisation spinal system - Malátová, Renata; Pucelík, Jirí; Rokytová, Jitka; Kolár, Pavel (Neuro endocrinology letters, 2008)
Information regarding two versions of an instrument called a muscle dynamometer, which enables detailed information about muscle activity in the deep stabilisation spinal system (DSSS), presented in this article. The MD01 (muscle dynamometer ver. 01) is a simple electromechanical instrument that allows measurement of muscle activity in two areas of the lumbar spine region. Measurements on patients have confirmed the usefulness of quantifying the initial state of a patient before rehabilitation as well as monitoring rehabilitation treatment; the MD01 is a suitable device for obtaining these measurements. However, a new and improved version of the MD01, the MD02, has been developed. The MD02 allows measurements in four different body regions and now has a PC interface, which allows achieving of patient information and data export for use with statistical software.
Keywords: uživatelské rozhraní počítače; Software; software; Muscle, Skeletal; bederní obratle; Muscle Strength Dynamometer; bolesti zad; kosterní svaly; Back Pain; Humans; lidé; User-Computer Interface; Lumbar Vertebrae; svalová síla - dynamometr